2009
DOI: 10.1111/j.1442-2042.2008.02214.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin replacement on ejaculatory dysfunction in streptozotocin‐induced diabetic rats

Abstract: Objectives:To investigate the effects of insulin replacement on ejaculatory dysfunction in streptozotocin (STZ)-induced diabetic rats. Methods: Rats were divided into three groups: (i) STZ-treated group; (ii) STZ-treated + insulin replacement (5 and 2 international units [IU]) group; and (iii) control group. The ejaculatory function in rats was evaluated using the spontaneous seminal emission (SSE) test. The amount of seminal vesicle fluid (SVF) stored in seminal vesicle was measured after the SSE test. Blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 8 publications
(22 reference statements)
2
21
0
Order By: Relevance
“…Although some studies have reported beneficial effects of insulin treatment on some aspects of sexual function such as copulatory behavior and ejaculation (Steger & Kienast 1990, Yonezawa et al 2009), few are the reports regarding the effects of insulin on erectile dysfunction (ED). Yet, this process also seems to be prone to the action of insulin.…”
Section: Ejaculatory and Erectile Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies have reported beneficial effects of insulin treatment on some aspects of sexual function such as copulatory behavior and ejaculation (Steger & Kienast 1990, Yonezawa et al 2009), few are the reports regarding the effects of insulin on erectile dysfunction (ED). Yet, this process also seems to be prone to the action of insulin.…”
Section: Ejaculatory and Erectile Functionmentioning
confidence: 99%
“…Studies in diabetic individuals or in diabetic conditions, provided important insights concerning the importance of insulin (its absence or excess) to the male reproductive system, with several studies reporting that the reproductive changes found in diabetic individuals could be reverted or attenuated by insulin treatment (Seethalakshmi et al 1987, Gondos & Bevier 1995, Ikeda et al 2000, Yamanaka et al 2003, Kim & Moley 2008, Singh et al 2009, Yonezawa et al 2009, Schoeller et al 2012a.…”
Section: Data From Studies In Diabetic Individuals/conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key words: bioartificial endocrine pancreas, diabetic rats, streptozotocin Japan Diabetes is one of the causes of sexual dysfunction, inducing neuroendocrine dysfunction [11,13,19,21] and apoplexy [2] based on hyperglycemia and insulin insufficiency. Rats are usually used as a diabetic animal models as diabetes can be induced by streptozotocin (STZ) for observations of sexual behavior [18,21,22,23]. Both men and women can contract type 1 and 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Rats are usually used as a diabetic animal models as diabetes can be induced by streptozotocin (STZ) for observations of sexual behavior [18,21,22,23]. Both men and women can contract type 1 and 2 diabetes.…”
mentioning
confidence: 99%